Kontribusi Kekuatan Otot Lengan Dan Koordinasi Mata Tangan Terhadap Kemampuan Passing Bawah Bola Voli Klub Dishub Kota Pekanbaru - Febry, Febry; Ramadani, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this research was to determine the contribution of arm muscle strength and hand-eye coordination to the ability of underhand passing volleyball for the Pekanbaru City Transportation Agency. The type of this researchis multiple correlations. The population and sample in this study were 12 players from the Pekanbaru City Transportation Service Club. The research instrument used was an arm muscle strength test with push-ups, an eyehand coordination test, and a volleyball bottom passing test. Based on the results of the study, the conclusions in this research were: (1) There was a contribution of arm muscle strength to the ability to pass under the Pekanbaru City Transportation Agency's volleyball club by 58.06%, (2) There was a contribution of hand-eye coordination to theability to pass under the volleyball club Pekanbaru City Transportation Agency of 49.00%, (3) There is a contribution of arm muscle strength and hand-eye coordination to the ability to pass under the Pekanbaru City Transportation Agency volleyball club of 66.10%.